Economic Tendencies of the European and Latvian Medical Device Market - Semjonova Nadezhda (Economics and Business, 2020)
Due to ageing of the population in developed counties and increase of the demand for the healthcare worldwide, the industry of medical devices (MD) becomes one of the fast-growing businesses. The present paper analyses the current state of the MD sector in Europe and in Latvia on the basis of the data obtained from open sources. Review of the current situation in the MD sector has demonstrated that the MD field still is and will remain an attractive sector of economics. The growth of the EU MD market by 3.5 % per year is sustainable. The market is highly innovative and leaves enough room for small and mediumsize enterprises that provide up to 95 % of all MD sector turnover. This indicates that MD sector manufactures products with high added value that make the sector attractive for countries with limited resources, such as Latvia. Although key players on the market do not changes much, example from Ireland demonstrates that investment in human capital is an important pre-requisite for country’s success in the MD sector. Unfortunately, the development of the MD industry in Latvia is very slow, the growth is around 0.7 % per year that may be explained just by inflation. There is also a lack of information on the Latvian MD industry both for professionals and society.